2013
DOI: 10.1111/pbr.12067
|View full text |Cite
|
Sign up to set email alerts
|

Hybridization between Camelina sativa (L.) Crantz (false flax) and North American Camelina species

Abstract: The potential for gene flow between Camelina sativa, a promising edible and industrial oil crop in Canada, and its wild North American relatives C. alyssum, C. microcarpa and C. rumelica subsp. rumelica, was investigated. Sequence analysis of the nuclear ribosomal internal transcribed spacer region (ITS) was used to differentiate Camelina species and/or accession‐specific nucleotide markers and identify interspecific F1 hybrids. ITS analysis identified hybrids in progeny of C. alyssum × C. sativa, C. microcarp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 9 publications
2
32
0
Order By: Relevance
“…Genomic DNA extraction and ITS sequencing followed the methods described in Séguin‐Swartz et al. (). Sequences were assembled and edited using the software Sequencher v.4.7 (Gene Codes Corporation, Ann Arbor, Michigan, USA 2006).…”
Section: Methodsmentioning
confidence: 99%
“…Genomic DNA extraction and ITS sequencing followed the methods described in Séguin‐Swartz et al. (). Sequences were assembled and edited using the software Sequencher v.4.7 (Gene Codes Corporation, Ann Arbor, Michigan, USA 2006).…”
Section: Methodsmentioning
confidence: 99%
“…The possibility of gene flow integrating herbicide tolerance into weeds and crop wild relatives is a reality in Canada, and this phenomenon is accelerating. An example was provided by Séguin-Swartz et al (2013) for species within the genus Camelina that are naturalized in Canada. Martin et al (2015) showed that the more distant Capsella bursa-pastoris (L.) Medik., which is also a neophyte in Canada, produces offspring when pollinated with the cultivated species Camelina sativa (L.) Crantz.…”
Section: In Situ Conservationmentioning
confidence: 99%
“…The collections of C. microcarpa species in different genebanks suggest that it has a diverse range of origin including the Mediterranean region, Armenia (Brock et al 2018), Germany, Poland, Czechia, Slovakia andGeorgia (Martin et al 2017;Smejkal 1971). Diversity studies, analyses of genome size and chromosome number along with the success of hybridization efforts between C. microcarpa and C. sativa (Séguin-Swartz et al 2013;Martin et al 2019) suggested the close relationship between these two species (Brock et al 2018;Martin et al 2017). However, not all the results were so encouraging with varying levels of hybridization success depending on the genotype (Séguin-Swartz et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Diversity studies, analyses of genome size and chromosome number along with the success of hybridization efforts between C. microcarpa and C. sativa (Séguin-Swartz et al 2013;Martin et al 2019) suggested the close relationship between these two species (Brock et al 2018;Martin et al 2017). However, not all the results were so encouraging with varying levels of hybridization success depending on the genotype (Séguin-Swartz et al 2013). These results were likely due to confusion with the classification of C. microcarpa accessions, either due to disparities in chromosome number and/or crosses being attempted with completely different species such as C.…”
Section: Introductionmentioning
confidence: 99%